Bahasa Melayu dalam warkah Melayu terpilih (Jurnal Bahasa, 2001)
This study is concerned with an analysis of the linguistic aspects of eight selected Malay letters written in the period from the 16 th to the 19th century. The data was extracted from The Legacy of the Malay Letter (1994) compiled by Annabel Teh Gallop from the British library, London. This micro study is based on the diachronic approach and attempts to discover the linguistic characteristics of the Jawi spelling system, morphology and vocabulary. In general, the findings show that: (i) There are similarities and differences in the Jawi spelling system, morphology and vocabulary in the selected Malay letter; and (ii) The selected Malay letters provide a significant impression of the usage of the Malay language across f our centuries